Bất định chính sách kinh tế của Trung Quốc và rủi ro sụp đổ giá cổ phiếu của doanh nghiệp Việt Nam - Nguyen Thu, Hien (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Using a dataset on stock price crash risk for 713 companies listed on Vietnamese stock exchanges from 2010 to 2023, the author find evidence that economic policy uncertainty in China increases the risk of stock price crash of Vietnamese listed firms. The results are robust across various components of economic policies in China and with different measures of stock price crash risk. The impact of policy uncertainty in China on stock price crash risk of Vietnamese firms occurs through three channels, including investor expectation discrepancy, the proportion of institutional shareholder ownership, and the proportion of independent board members. The study suggests that to reduce the risk of stock price crash, Vietnamese firms need to improve mechanisms to enhance corporate governance and reduce discrepancies in investor expectations.
Keywords: Economic policy uncertainty; Vietnam stock market; Stock crash